2021
DOI: 10.1029/2020jb020242
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Approach to Mapping Regimes of Earthquake‐Induced Static Stress Changes Acting on Magmatic Pathways

Abstract: Magmatic intrusions are generally mode I fractures and so preferentially open parallel to the minimum principal stress direction (σ 3), although they may be influenced by structures or weaknesses in the host rock such as faults,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 128 publications
(188 reference statements)
0
1
0
Order By: Relevance
“…Numerous studies have demonstrated the correlation between positive ΔCFS and increased seismic activity or negative ΔCFS with zones of post‐earthquake quiescence (e.g., Árnadóttir et al., 2004; King et al., 1994; Lin & Stein, 2004; Pope & Mooney, 2020). The CFS changes can also affect magmatic systems by triggering volcanic unrest and eruption (Biggs et al., 2013; Jenkins et al., 2021) and increase crustal permeability by channeling fluids to the seafloor (Bonini, 2019).…”
Section: Future Seismic Hazardsmentioning
confidence: 99%
“…Numerous studies have demonstrated the correlation between positive ΔCFS and increased seismic activity or negative ΔCFS with zones of post‐earthquake quiescence (e.g., Árnadóttir et al., 2004; King et al., 1994; Lin & Stein, 2004; Pope & Mooney, 2020). The CFS changes can also affect magmatic systems by triggering volcanic unrest and eruption (Biggs et al., 2013; Jenkins et al., 2021) and increase crustal permeability by channeling fluids to the seafloor (Bonini, 2019).…”
Section: Future Seismic Hazardsmentioning
confidence: 99%